Institutionalization of the sustainable development goals in agro-industries - Liszbinski, Bianca Bigolin; Brizolla, Maria Margarete Baccin; Patias, Tiago Zardin (Revista de Administração da UFSM, 2024)
Purpose: To analyze the relationship between the institutionalization process by isomorphic mechanisms and the adhesion of agro-industries to the sustainable development goals. Methodology: This is a descriptive study, with quantitative application, operationalized through a survey in a sample with 254 agri-food industries in the State of Rio Grande do Sul and by adopting the structural equation modeling technique for the measurement model and the structural model analysis. Results: The hypothesis that institutionalization through isomorphic mechanisms is positively associated with the implementation of sustainable development goals is confirmed, with an emphasis on the significance of all isomorphic variables analyzed, that is, coercive, normative, and mimetic isomorphism. Research limitations and implications: Despite the important observations found, this research has limitations regarding the adopted quantitative method, with the common method bias and the overfitting being necessary to validate the estimated model. Regarding implications, the research results contribute to the theoretical and practical subject field, opening up new possibilities for analyzing the engagement of organizations with the sustainable development goals from the institutional theory perspective. Originality: The study on the engagement of companies with the sustainable development goals is considered recent and lacking progress in the literature; thus, this study moves forward in understanding this phenomenon, especially on institutional issues that are decisive for the involvement of agro-industries in this sustainable development agenda.